Dolžen bytʹ. Serhej Taranov = Shall be by Serge Taranov - Rubanenko, Mahomed (Bogoslovs'ki rozdymi, 2021)
New edition review: Должен быть. Сергей Таранов. Киев: Четверта хвиля, 2021. 168 С.; ISBN 978-966-529-349-1.